Molecular Mechanisms for the Coupling of Endocytosis to Exocytosis in Neurons - Xie, Zhenli; Long, Jiangang; Liu, Jiankang; Chai, Zuying; Kang, Xinjiang; Wang, Changhe (Frontiers in Molecular Neuroscience, 2017)
Neuronal communication and brain function mainly depend on the fundamental biological events of neurotransmission, including the exocytosis of presynaptic vesicles (SVs) for neurotransmitter release and the subsequent endocytosis for SV retrieval. Neurotransmitters are released through the Ca2+- and SNARE-dependent fusion of SVs with the presynaptic plasma membrane. Following exocytosis, endocytosis occurs immediately to retrieve SV membrane and fusion machinery for local recycling and thus maintain the homeostasis of synaptic structure and sustained neurotransmission. Apart from the general endocytic machinery, recent studies have also revealed the involvement of SNARE proteins (synaptobrevin, SNAP25, and syntaxin), synaptophysin, Ca2+/calmodulin, and members of the synaptotagmin protein family (Syt1, Syt4, Syt7, and Syt11) in the balance and tight coupling of exo-endocytosis in neurons. Here, we provide an overview of recent progress in understanding how these neuron-specific adaptors coordinate to ensure precise and efficient endocytosis during neurotransmission.